Analysis of the Effect of Leadership Style and Work Culture on Organizational Commitment with Work Motivation as an Intervening Variable in Nurses at Hermina Serpong Hospital - Jannah, Ana Raudah Al; Mulyani, Erry Yudhya; Tahjoo, Anastina (Ridwan Institute, 2023)
Hospital is one form of organization engaged in health services. This health service is always demanded to always get better. Hermina Serpong Hospital is a type C private hospital in South Tangerang City that provides health services for patients and is committed to providing services in accordance with nursing standards by optimizing nurses' organizational commitment. This study aims to analyze the effect of leadership style and work culture on nurses' organizational commitment with work motivation as an intervening variable. Research with a quantitative approach and survey method using a questionnaire. The population is all nurses at Hermina Serpong Hospital. The sampling technique is using total sampling with a sample size of 99 respondents. The data analysis method uses path analysis structural equation model (Structural Equation Model). Research results: There is an influence of leadership style and work culture on nurses' organizational commitment with work variables as intervening variables. Managerial implications: The management of Hermina Sepong Hospital builds the spirit of the leadership style of the superiors and enhances a positive work culture so as to increase the work motivation of the nurses which will increase the nurses' commitment to work.